FRAUD PENTAGON THEORY: ALAT DETEKSI FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI INDONESIA, MALAYSIA, SINGAPURA - Ybanez Vijeysechan Hamadi; Daniel Sugama Stephanus; Dian Wijayanti (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
This study examine the dimensions of fraud pentagon to explain this effect on the financial statement fraud. The fraud pentagon theory shows five elements can affect financial statement fraud, the element of pressure, the element of opportunity, the element of rationalization, the element of competence, and the element of arrogance. The variables of fraud pentagon are proxied by the leverage ratio, nature of industry, audit opinion, changes in the board of directors, and dualism position. The detection of financial statement fraud in this research uses the f-score model. The data used is secondary data obtained from company annual reports and company financial reports in the property and real estate sector in Indonesia, Malaysia, and Singapore for the period 2018-2019. Data was analyzed by using descriptive statistical analysis and logistic regression analysis. The test result showed that leverage ratio, nature of industry, and dualism position had a negative effect on the prediction of financial statemen fraud, while audit opinion and changes in the board of directors had no effect on the prediction of financial statement fraud.